TRAINING IN THE MAKING OF DAYAK CLOTHES FOR STUDENTS OF SMKN 3 PALANGKA RAYA - Achmad Zainul Rozikin; Endang Sri Suyati; Muhammad Ziaurrahman (BAKTIMU : Jurnal Pengabdian Kepada Masyarakat, 2023)
Environmental issues cannot be separated from issues of the creative industry and the creative economy. Environmental issues have become one of the important issues discussed in the global community. Responding to the issue of jute waste above, it is necessary to have activities that are beneficial to the community, namely providing an understanding of the daers of waste from jute and training on the use of jute. The method of this service activity is in the form of training for students of SMK Negeri 3 in order to reduce jute sack waste in Palangka Raya City. This training does not have to be from the government, but can also be done by other agencies such as universities. Universities have an obligation to serve the community according to the contents of the Tri Dharma of Higher Education. The conclusion of this study is that this activity is an effort to increase understanding of the dangers of waste, especially inorganic waste, awareness of the importance of preserving the environment to improve physical and mental health, and utilizing skills as business opportunities.